Conditional: if-else
if-else
if ( i == j ) $s1 i      
  i++ ; $s2 j      
else
  j-- ;
j += i ;
As before, if the condition is false, we want to jump.
      bne  $s1, $s2, ELSE   # branch if !( i == j )
      addi $s1, $s1, 1      #    i++
ELSE: addi $s2, $s2, -1     # else j--
      add $s2, $s2, $s1     # j += i
What's wrong with this picture?
Once we've done the if-body, we need to jump over the else-body
      bne  $s1, $s2, ELSE   # branch if !( i == j )
      addi $s1, $s1, 1      #    i++
      j NEXT                #    jump over else
ELSE: addi $s2, $s2, -1     # else j--
NEXT:   add $s2, $s2, $s1   # j += i